Real-time price discovery via verbal communication: Method and application to Fedspeak - Gómez-Cram, Roberto; Grotteria, Marco (Journal of Financial Economics, 2022)
We study the price discovery process on FOMC days. For several asset classes, we find that price movements around the post-meeting statement release are strong predictors of price movements around the subsequent press conference. The correlation is 58% for medium-term Eurodollar futures and 44% for the S&P500 index. We then time-stamp the words pronounced in press conference videos and align these words with high-frequency financial data. Minutes in which the chairman discusses changes in the newly issued policy statement underlie the positive correlation. We discuss potential explanations and consider the implications of our findings for asset pricing and monetary economics.